2007
DOI: 10.1111/j.1654-1103.2007.tb02523.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the floristic continuum: Ordination space position estimated from imaging spectroscopy

Abstract: Objective: To present a non-classificatory technique of map representation of compositional patterns of vegetation as no two plant species assemblages are completely alike and gradations often occur. Variation is depicted as continuous fields instead of classes. Location: Murnauer Moos, Bavaria. Methods: The study combined vegetation ecology and remote sensing methods. The gradual representation of compositional patterns was based on techniques of ordination and regression, instead of mapping class fractions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 38 publications
1
71
0
Order By: Relevance
“…Regarding the grassland classes, the classification obtained in this study is as accurate as those obtained in studies comparing vegetation and micro-topography using LIDAR data to classify wetland areas (Moeslund et al, 2011). Several studies indicated that vegetation species in wetlands can be identified using hyperspectral data (Schmidtlein et al, 2007). From the perspective of this study, this method could be assessed to classify wetland vegetation at the dominant-species level using TerraSAR-X data.…”
Section: Tablementioning
confidence: 87%
“…Regarding the grassland classes, the classification obtained in this study is as accurate as those obtained in studies comparing vegetation and micro-topography using LIDAR data to classify wetland areas (Moeslund et al, 2011). Several studies indicated that vegetation species in wetlands can be identified using hyperspectral data (Schmidtlein et al, 2007). From the perspective of this study, this method could be assessed to classify wetland vegetation at the dominant-species level using TerraSAR-X data.…”
Section: Tablementioning
confidence: 87%
“…The use of biogeographical gradients in non-linear ordinations combines the information from vegetation ecology and remote sensing methods (Schmidtlein et al, 2007). The approach entails analysing trends present in sets of floristic variables and establishing the nature of interrelationship between them (Armitage et al, 2004).…”
Section: Vegetation Patterns and Indicesmentioning
confidence: 99%
“…Reflectance values have been related to ordination axes by PLSR and the resulting regression equations were then applied on the spectral image. By this method the compositional variation was mapped for an area of 25 ha (R 2 = 0.79), using continuous fields (Schmidtlein et al, 2007). Such biogeographical patterns can be related to precipitation, temperature and soil conditions on a regional scale (Mahecha and Schmidtlein, 2008;Schmidt and Hewitt, 2004).…”
Section: Vegetation Patterns and Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial heterogeneity of a peatland surface is such that in practice, these requirements are very difficult to fulfil. Combined ordination and regression approaches have been developed to try and overcome some of the limitations of mapping approaches that require vegetation to be categorised a priori (Schmidtlein, Zimmermann, Schüpferling, & Weiβ, 2007) and the need for homogenous plant coverage at the spatial resolution of the sensor. Typically, ordination methods are used to assign numerical values (i.e., ordination scores) to plot-level species data, which relate to the level of floristic similarity or dissimilarity between plots.…”
Section: Introductionmentioning
confidence: 99%